Nasogastric vs. Intravenous Rehydration in Children with Gastroenteritis and Refusal to Drink: A Randomized Controlled Trial - Marquard, J.; Lerch, C.; Rosen, A.; Wieczorek, H.; Mayatepek, E.; Meißner, T. (Klinische Pädiatrie, 2014)
Nasogastric rehydration therapy (NGRT) is the recommended therapy in moderately dehydrated children with gastroenteritis and refusal to drink, since it is supposed to be as effective if not better than intravenous rehydration therapy (IVRT). However, in clinical practice IVRT is often favored. We conducted a clinical trial to determine whether IVRT is not inferior to NGRT.Children 3 months to 6 years of age with moderate dehydration and refusal to drink secondary to gastroenteritis were recruited. After clinical assessment of the degree of dehydration, patients were assigned randomly to receive either IVRT or NGRT over 6 h on the hospital ward.Recruitment did not yield the estimated number of patients. Mainly, non-enrollment was due to failure to obtain parental consent because IVRT was expected. 97 patients were enrolled in the study, 46 were randomized to NGRT and 51 to IVRT. There was no difference between IVRT and NGRT groups concerning length of hospital stay (2.2±1.1 days vs. 2.4±1.1 days), success of rehydration (78 vs. 76%) and adverse events.Since we had to terminate the study ahead of schedule due to a low recruiting rate, our results are not reliable. However, data from the literature shows that the widespread described superiority of NGRT over IVRT is seriously influenced by studies from developing countries questioning the applicability of the results to a setting available in high-income countries nowadays.Our study demonstrates the difficulties performing such a study in a high-income country to come to an objective and clearly evident final conclusion.
Keywords: gastroenteritis; moderate dehydration; nasogastric rehydration therapy; intravenous rehydration therapy; children